UNDIFFERENTIATED EPILEPTIC AURA IN CHILDREN - M. R. Kremenchugskaya; E. I. Barletova; O. V. Globa; L. Yu. Glukhova; K. Yu. Mukhin (Эпилепсия и пароксизмальные состояния)
Authors of the current article have made clinic- electroencephalographic and neurovisualisative analysis of group of 85 patients with different forms of focal epilepsies with indications to epileptic aura. It was established that in 6% of cases clinical manifestations of aura didn’t match the criteria described in classification of epileptic aura by Cleveland Clinic Foundation, Ohio, USA. These stereotypic feelings, occurring before epileptic seizure of another character or isolated and described by patients as «unexplainable feeling, prompting the upcoming the seizure» was proposed to name as undifferentiated aura. As a result of detailed analysis of group patients with undifferentiated aura was established, that in most of the cases there was link between clinical manifestation of epilepsy, including auras, and temporal region of brain cortex. Authors demonstrate these standing points with clinical case of patient with focal epilepsy and undifferentiated auras. The article contains proposal for optimization of focal epilepsy with undifferentiated auras diagnostics.